A novel Aroclor 1242-degrading culturable endophytic bacterium isolated from tissue culture seedlings of Salix matsudana f. pendula Schneid. (February 2018) - Cai, Man; Song, Ge; Li, Yuling; Du, Kejiu
Graphical abstract: Highlights: Endophytic bacteria were isolated from Salix matsudana f. pendula . The strain CGL-1 had PCBs-removing ability. The strain CGL-1 was identified as Enterobacter sp. Abstract: With this study, we aimed to isolate the most promising bacteria to enhance persistent environmental pollutants (Aroclor 1242) phytoremediation from Salix. matsudana f. pendula Schneid, which has wide distribution and adaptability characteristics. A total of 12 endophytic bacteria strains were isolated and purifed from both Salix. matsudana f. pendula Schneid and its tissue culture seedlings. Of which, the strains CGL-1, SGL-1, SPL-3, 8, 17 and 24 were further isolated by enrichment culture with Aroclor 1242 as the sole source of carbon and energy. Compared with the growth characteristic of these strains, strain CGL-1 growth well under higher concentration of Aroclor 1242 exposure than others. The strain CGL-1 was identified as Enterobacter sp. with respect to 16S ribosomal DNA sequences, colony morphology and cell morphological characteristics. The optimum culture condition of the CGL-1 for removing Aroclor 1242 was optimized as: 27–32 °C, pH 7.0, NaCl ≦ 1%, inoculum 10%. Under these conditions, the removing ratio could reach to 43.2% after 7 d. The strain CGL-1 appears to be the most promising bacterium to enhance Aroclor 1242 phytoremediation. The endophytic bacterium is potentially useful for helping plants to tolerate pollutant stress and for increasing bioremediation resources.